Психологія стресу : конспект лекцій для здобувачів вищої освіти другого (магістерського) рівня денної та заочної форм здобуття освіти за спеціальністю 011 «Освітні, педагогічні науки» [Електронний ресурс] - Білоцерківська, Юлія Олександрівна; Bilotserkivska, Yuliia (Харків : Харківський національний університет імені В. Н. Каразіна, 2025)
Конспект лекцій з дисципліни «Психологія стресу» спрямований на формування у здобувачів освіти системного розуміння основних понять та характеристик стресу і стресових реакцій, чинників стресу, наслідків тривалого впливу стресорів, особливостей посттравматичного стресового розладу та кризи горя, а також критеріїв оцінювання рівня стресу і методів його профілактики. Розробка складається з 10 тем і містить основні концепції, теорії, підходи та практичні інструменти психології стресу, що сприятимуть опануванню навичок діагностики, профілактики та подолання стресів в освітньому середовищі. Видання призначене для здобувачів освіти другого (магістерського) рівня вищої освіти денної та заочної форм здобуття освіти за спеціальністю 011 «Освітні, педагогічні науки».

The lecture notes on the discipline «Psychology of stress» are aimed at developing in students a systematic understanding of the basic concepts and characteristics of stress and stress reactions, stress factors, the consequences of prolonged exposure to stressors, the features of post-traumatic stress disorder and grief crisis, as well as criteria for assessing the level of stress and methods for its prevention. The development consists of 10 topics and contains the main concepts, theories, approaches and practical tools of stress psychology, which will contribute to mastering the skills of diagnosing, preventing and overcoming stress in the educational environment. The publication is intended for students of higher education of the second (master’s) level in the full-time and part-time majoring in specialty 011 «Educational and pedagogical sciences».
Psychology of stress : lecture notes for students higher education of the second (master’s) level full-time and part-time majoring in the specialization 011 «Educational and pedagogical sciences» [Electronic resource]
В авторській редакції
Keywords: SOCIAL SCIENCES::Social sciences::Education; SOCIAL SCIENCES::Social sciences::Psychology; стрес; психологія стресу; професійний стрес; стресостійкість; критерії оцінки стресу; профілактика стресу; stress; psychology of stress; occupational stress; stress resilience; stress assessment criteria; stress prevention